Digital Literacy of Social Media Users in Preventing Online Gender-Based Violence in Indonesia - Setyaningsih, Rila; Santoso, Didik Haryadi; Nurwahid, Aditya Fahmi (Journal of Ecohumanism, 2024)
Online Gender-Based Violence (OGBV) is violence committed against a person based on gender or gender with the help of digital technology. Women are the most vulnerable group to becoming victims of OGBV, although it is possible that men can also be victims. It is important for social media users to have online resilience or the ability to deal with negative risks in the online world. This study explores the types of OGBV that occur and efforts to prevent recurrence of cases. This study uses a constructivist paradigm with a qualitative research design with the type of case study. The subjects in this study consisted of six people. Interviews, observations, and documentation are the data collection techniques used in this study. Data analysis in the study consists of several steps (i.e., data reduction, data presentation, and drawn conclusions) as well as triangulation and source triangulation techniques to ensure the validity of the research data. This study found several types of online gender-based violence experienced by victims. These types of online gender-based violence are verbal harassment and bullying, account hacking, cyberstalking, and threats of sexual violence. The victims already have digital literacy skills to prevent the recurrence of the case. Digital literacy in question is in the form of efforts to maintain digital security on the social media accounts used. These findings are an important basis for the development of more effective and appropriate policies and intervention programs in accordance with local conditions.